Gas Hydrate Accumulation and Occurrence Associated with Cold Seep Systems in the Northern South China Sea: An Overview - Wei Zhang; Jinqiang Liang; Qianyong Liang; Jiangong Wei; Zhifeng Wan; Junxi Feng; Wei Huang; Jing Zhao; Miaomiao Meng; Wei Deng; Chongmin Chen (Geofluids)
Studying deep-water cold seep systems is of great significance to gas hydrate exploration due to their close relationship. Various cold seep systems and related gas hydrate accumulations have been discovered in the northern South China Sea in the past three decades. Based on high-resolution seismic data, subbottom profiles, in situ submergence observations, deep drilling and coring, and hydrate gas geochemical analyses, the geological and geophysical characteristics of these cold seep systems and their associated gas hydrate accumulations in the Qiongdongnan Basin, the Shenhu area, the Dongsha area, and the Taixinan Basin have been investigated. Cold seep systems are present in diverse stages of evolution and exhibit various seabed microgeomorphic, geological, and geochemical features. Active cold seep systems with a large amount of gas leakage, gas plumes, and microbial communities and inactive cold seep systems with authigenic carbonate pavements are related to the variable intensity of the gas-bearing fluid, which is usually derived from the deep strata through mud diapirs, mud volcanoes, gas chimneys, and faults. Gas hydrates are usually precipitated in cold seep vents and deeper vertical fluid migration pathways, indicating that deep gas-bearing fluid activities control the formation and accumulation of gas hydrates. The hydrocarbons collected from cold seep systems and their associated gas hydrate reservoirs are generally mixtures of biogenic gas and thermogenic gas, the origin of which is generally consistent with that of deep conventional gas. We also discuss the paragenetic relationship between the gas-bearing fluid and the seafloor morphology of cold seeps and the deep-shallow coupling of gas hydrates, cold seeps, and deep petroleum reservoirs. It is reasonable to conclude that the deep petroleum systems and gas-bearing fluid activity jointly control the development of cold seep systems and the accumulation of gas hydrates in the northern South China Sea. Therefore, the favorable areas for conventional oil and gas enrichment are also prospective areas for exploring active cold seeps and gas hydrates.